Managing municipal waste in China from a standpoint of social governance. Issue 1 (June 2022) - Zhang, Min; Ma, Ying; Liu, Mengmei; Zhang, Huijuan; Lee, Yunsoo
The research on municipal waste management is getting some traction from both scholars and practitioners. However, few studies have systematically reviewed this issue in China. Therefore, the purpose of our paper is to respond to this lacuna by systematically reviewing the research on urban waste management in China. In addition, we addressed the difficulties encountered by multiple stakeholders with respect to municipal waste management and provide a coherent understanding from a social governance perspective. Drawing on a systematic literature review, we analyzed 40 papers on social governance of waste management. The synthesis of previous studies demonstrates that although government deserves credit for guiding other actors, it cannot effectively safeguard the interests of all stakeholders. We integrated previous findings and gleaned suggestions for governments to implement strategic waste management.